The Leadership of Jean Valjean in Les Miserable Movie Directed by Tom Hooper - Mardewi, Tati; Larashandy, Heydi Ruth; Indriyani, Furi; Dewi, Nurmala; Larashandy, Larashandy; Dewi, Dewi (English Education:Journal of English Teaching and Research, 2021)
The goal of the research is to analyze the leadership that Jean Valjean shown in Les Miserables Movie directed by Tom Hooper. This research focuses on two aspects, the type and the impact of the leadership. The type of leadership that are found in this movie are (1) Laissez-faire leadership and (2) Servant leadership. While There are three impact of leadership that indeed to Jean Valjean as the main character in Les Miserables, they are (1) Inspiring confidence for others (2) Creating a respectful environment and (3) Increasing loyalty and trust. The Les Miserables Movie is a perfect movie for analyzing leadership, as it tells about the life of Jean Valjean who tries keeping himself in fire even though there are so many inside and outside difficulties in his life as a prisoner and after he has been released on parole. According to (Almaki et al., 2016) leadership is not just about power and authority, but it is a set of characteristics that should be owned by the leader. This movie shows many things to be a good leader who can bring a big impact to people. As a leader we must have faith, forgive the enemies and belief, there will always be a brighter tomorrow. We are all leaders in our lives. So, this movie gives us so many things that we can learn to have better life.